Fgf8 regulates first pharyngeal arch segmentation through pouch-cleft interactions - Zbasnik, Nathaniel; Fish, Jennifer L. (Frontiers in Cell and Developmental Biology, 2023)
Introduction: The pharyngeal arches are transient developmental structures that, in vertebrates, give rise to tissues of the head and neck. A critical process underlying the specification of distinct arch derivatives is segmentation of the arches along the anterior-posterior axis. Formation of ectodermal-endodermal interfaces is a key mediator of this process, and although it is essential, mechanisms regulating the establishment of these interfaces vary between pouches and between taxa. Methods: Here, we focus on the patterning and morphogenesis of epithelia associated with the first pharyngeal arch, the first pharyngeal pouch (pp1) and the first pharyngeal cleft (pc1), and the role of Fgf8 dosage in these processes in the mouse model system. Results: We find that severe reductions of Fgf8 levels disrupt both pp1 and pc1 development. Notably, out-pocketing of pp1 is largely robust to Fgf8 reductions, however, pp1 extension along the proximal-distal axis fails when Fgf8 is low. Our data indicate that Fgf8 is required for specification of regional identity in both pp1 and pc1, for localized changes in cell polarity, and for elongation and extension of both pp1 and pc1. Discussion: Based on Fgf8-mediated changes in tissue relationships between pp1 and pc1, we hypothesize that extension of pp1 requires physical interaction with pc1. Overall, our data indicate a critical role for the lateral surface ectoderm in segmentation of the first pharyngeal arch that has previously been under-appreciated.